Strain-induced isosymmetric phase transition in BiFeO3 - EDERER, CLAUDE (American Physical Society, 2010)
We calculate the effect of epitaxial strain on the structure and properties of multiferroic bismuth ferrite, BiFeO3, using first-principles density-functional theory. We investigate epitaxial strain corresponding to an (001)-oriented substrate and find that, while small strain causes only quantitative changes in behavior from the bulk material, compressive strains of greater than 4% induce an isosymmetric phase transition accompanied by a dramatic change in structure. In striking contrast to the bulk rhombohedral perovskite, the highly strained structure has a c/a ratio of similar to 1.3 and five-coordinated Fe atoms. We predict a rotation of polarization from [111] (bulk) to nearly [001], accompanied by an increase in magnitude of similar to 50%, and a suppression of the magnetic ordering temperature. Our calculations indicate critical strain values at which the two phases might be expected to coexist and shed light on recent experimental observation of a morphotropic phase boundary in strained BiFeO3.
PUBLISHED
Keywords: Physics; POLARIZATION